2012
DOI: 10.2135/cropsci2011.04.0185
|View full text |Cite
|
Sign up to set email alerts
|

High Degree of Genetic Variation of Winter Hardiness in a Panel of Beta vulgaris L.

Abstract: Growing sugar beet (Befa vulgaris L. subsp, vulgaris [sugar beet cultivar group]) as a winter crop requires the development of a winter sugar beet with controlled bolting and sufficient winter hardiness. To evaluate the genetic variation for winter hardiness in B. vulgaris L,, we determined the survival rate (SR) in a panel of 396 accessions tested in eight overwintering field trials in Germany and Belarus, The panel included the cultivar groups sugar beet, fodder beet, garden beet, and leaf beet, as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…Across all four environments, bolting rates for the 41 accessions ranged from 0.05 to 0.75 (Figure 1). Variation for survival rate survival rate after winter across eight environments in 2008/09 and 2009/10 was described in detail by Kirchhoff et al [32], and ranged from 0.07 to 0.66. On average, sugar beet accessions performed best (0.39) while fodder beet and garden beet performed worst (0.24 and 0.19, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Across all four environments, bolting rates for the 41 accessions ranged from 0.05 to 0.75 (Figure 1). Variation for survival rate survival rate after winter across eight environments in 2008/09 and 2009/10 was described in detail by Kirchhoff et al [32], and ranged from 0.07 to 0.66. On average, sugar beet accessions performed best (0.39) while fodder beet and garden beet performed worst (0.24 and 0.19, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…This panel had been phenotyped before for variation in the occurrence of bolting before winter (i.e. in the absence of vernalization) and survival rates after winter [32]. As candidate genes we chose (i) BTC1 and (ii) BvFT1 , because of their known functions in the regulation of vernalization requirement and response in beet, and (iii) BvFL1 , because of the regulatory role of its homolog FLC in both vernalization and cold stress response in Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%
“…In overwintering field trials in 2008/2009 with 396 B. vulgaris accessions described by Kirchhoff et al (2012), sugar beet accession BETA 1773 showed a high level of post-winter bolting resistance across three locations. Fifty percent of the plants of this accession did not bolt until middle of June of the second year when the experiment was completed (unpublished data).…”
Section: Introductionmentioning
confidence: 98%
“…As a result, plants in temperate regions have developed mechanisms to endure the low temperature stress during winter [17][18][19] . But the ability of the plant to resist frost can be measured by the lethal temperature of plant tissue [20,21] . The temperature is generally regarded as the one at which about 50% to 90% of plants' reproductive organs could be killed [22][23][24] .…”
Section: Introductionmentioning
confidence: 99%